2008
DOI: 10.1002/mus.21116
|View full text |Cite
|
Sign up to set email alerts
|

Location of collateral sprouting of donor nerve following end‐to‐side neurorrhaphy

Abstract: Various studies have demonstrated collateral regeneration of the donor nerve following end-to-side neurorrhaphy, but the location of collateral sprouting remains controversial. In a rat end-to-side neurorrhaphy model we isolated nerve fibers from the donor nerve at the neurorrhaphy site utilizing a micro-tease technique. We found that axons sprouted collaterally from a myelinated nerve fiber at the node of Ranvier. Based on this preliminary result we conclude that myelinated nerve fibers could sprout collatera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 21 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…The origin of the axons has been demonstrated with double label techniques from Ranvier’s nodes proximal to coaptation site [ 61 ], but the level has been questioned, with some authors believing the closest Ranvier nodes to be involved [ 62 ] and other papers [ 11 , 63 ] claiming for a role played by more proximal structures. Maybe these different opinions have been produced by different techniques and methods of investigation, as just noted [ 64 ]: the former study [ 62 ] had been conducted on an epineurial window model (see below c) and using electrophysiological registration, and the latter by simple suture (see below c) to the donor nerve and double retrograde labelling technique [ 11 ] or epineurial window ad suturing (see below c), microtearing and histomorphometric analysis [ 63 ]. A role of interneuronal signalling in dorsal root ganglia had been claimed [ 65 ] and the hypothesis of a Central Nervous System origin has been recently regained [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…The origin of the axons has been demonstrated with double label techniques from Ranvier’s nodes proximal to coaptation site [ 61 ], but the level has been questioned, with some authors believing the closest Ranvier nodes to be involved [ 62 ] and other papers [ 11 , 63 ] claiming for a role played by more proximal structures. Maybe these different opinions have been produced by different techniques and methods of investigation, as just noted [ 64 ]: the former study [ 62 ] had been conducted on an epineurial window model (see below c) and using electrophysiological registration, and the latter by simple suture (see below c) to the donor nerve and double retrograde labelling technique [ 11 ] or epineurial window ad suturing (see below c), microtearing and histomorphometric analysis [ 63 ]. A role of interneuronal signalling in dorsal root ganglia had been claimed [ 65 ] and the hypothesis of a Central Nervous System origin has been recently regained [ 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, numerous end-to-side nerve repair studies in other small animals (rats and rabbits) have been shown to support nerve regeneration to various degrees. The suggested mechanisms are either terminal sprouting from damaged donor axons injured during epineurotomy (Hayashi et al, 2008) or collateral sprouting from the donor nerve (Bontioti et al, 2005; Lundborg et al, 1994; Tham and Morrison, 1998; Tiangco et al 2001; Viterbo et al, 1992 and 1998; Zhang et al 2000; Zhu et al, 2008). There has been concern that, due to the relatively short distances from the nerve transection to neurorrhaphy sites in many of these studies, these mostly good results could be due to contamination of regenerating axons from the proximal stump of the severed nerve (Al-Qattan and Al-Thunayan 1998; McCallister et al, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Completion of Wallerian degeneration and Schwann cell proliferation may lead to acceleration of motor end plate degeneration (19). From this perspective, most scholars think that neural repair shall occur as early as possible after nerve injury (20).…”
Section: Discussionmentioning
confidence: 99%